Professional “acme” – As a Factor for Developing Professional Identity - Dilmurod Abdusamiyev (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This study aims to examine the concept of "professional acme" as a significant determinant in the formation of professional identity among educators. Employing a theoretical and conceptual literature review methodology, the paper explores various stages of professional development and integrates psychological and pedagogical theories, including acmeology and identity formation frameworks. The results indicate that achieving "acme”, the peak of professional excellence requires continuous learning, intrinsic motivation, mentoring, and psychological resilience. Teachers who reach this stage demonstrate stronger identity, greater instructional impact, and contribute more significantly to educational quality and student development. The study recommends teacher education programs to integrate reflective practice, value formation, and mentorship structures to nurture professional maturity